Differentially expressed small RNAs in Arabidopsis galls formed by Meloidogyne javanica: a functional role for miR390 and its TAS3‐derived tasiRNAs. Issue 4 (6th November 2015) - Cabrera, Javier; Barcala, Marta; García, Alejandra; Rio‐Machín, Ana; Medina, Clémence; Jaubert‐Possamai, Stephanie; Favery, Bruno; Maizel, Alexis; Ruiz‐Ferrer, Virginia; Fenoll, Carmen; Escobar, Carolina
Summary: Root‐knot nematodes (RKNs) induce inside the vascular cylinder the giant cells (GCs) embedded in the galls. The distinctive gene repression in early‐developing GCs could be facilitated by small RNAs (sRNA) such as miRNAs, and/or epigenetic mechanisms mediated by 24nt‐sRNAs, rasiRNAs and 21‐22nt‐sRNAs. Therefore, the sRNA‐population together with the role of the miR390/TAS3/ARFs module were studied during early gall/GC formation. Three sRNA libraries from 3‐d‐post‐inoculation (dpi) galls induced by Meloidogyne javanica in Arabidopsis and three from uninfected root segments were sequenced following Illumina‐Solexa technology. pMIR390a::GUS and pTAS3::GUS lines were assayed for nematode‐dependent promoter activation. A sensor line indicative of TAS3 ‐derived tasiRNAs binding to the ARF3 sequence ( pARF3:ARF3‐ GUS) together with a tasiRNA‐ resistant ARF3 line ( pARF3:ARF3m‐GUS ) were used for functional analysis. The sRNA population showed significant differences between galls and controls, with high validation rate and correspondence with their target expression: 21‐nt sRNAs corresponding mainly to miRNAs were downregulated, whilst 24‐nt‐sRNAs from the rasiRNA family were mostly upregulated in galls. The promoters of MIR390a and TAS3, active in galls, and the pARF3:ARF3‐ GUS line, indicated a role of TAS3 ‐derived‐ tasiRNAs in galls. The regulatory module miR390/TAS3 is necessary for proper gall formation possibly through auxin‐responsive factors, and the abundance of 24‐nt sRNAs (mostly rasiRNAs) constitutes a gall hallmark.